Polystyrene nanoplastics shape microbiome and functional metabolism in anaerobic digestion. (1st July 2022) - Wang, Jing; Ma, Dongmei; Feng, Kun; Lou, Yu; Zhou, Huihui; Liu, Bingfeng; Xie, Guojun; Ren, Nanqi; Xing, Defeng
Highlights: The inhibited acidification by nanoplastics was dominant in sludge digestion. 50 nm nanoplastics inhibited methane production by anaerobic microorganisms. Toxicity of nanoplastics derives from oxidative stress induced by particle size. The presence of polystyrene nanoplastics reduced the abundance of functional genes. Nanoplastics reduced the abundances of mcrA and methanogens in anaerobic digestion. Abstract: Nanoplastics (NPs) and microplastics (MPs) are ubiquitous in the natural environment, social production, and life. However, our understanding of the effects of NPs and MPs on shaping the microbiome and functional metabolism of anaerobic microorganisms is limited. We investigated the response of core microbiomes and functional genes to polystyrene (PS) NPs and MPs exposure in a representative anaerobic micro-ecosystem of waste activated sludge. Independent anaerobic digestion (AD) experiment indicated that PS nanobeads suppressed acidogenesis by inhibiting the activity of acetate kinase, and subsequently reduced methane production. Our findings confirmed that MPs (1 and 10 μm) had no perceptible effect on methane production, yet 50 nm NPs resulted in a 15.5% decrease in methane yield, perhaps driven by the behavior of dominant genera Sulfurovum, Candidatus Methanofastidiosum, and Methanobacterium . Assays revealed that NPs contributed to the simplest network assemblies in bacterial communities, contrary to empirical networks in archaeal communities. NPs significantly reduced the abundance of genes involved in carbon degradation: lig, naglu and xylA, as well as gcd and phnK related to phosphorus cycling. The absolute abundance of mcrA encoding methyl-coenzyme M reductase was 54.4% of the control assay. PS NPs might adversely affect the biodiversity and biogeochemical cycles in natural and artificial ecosystems through their negative impact on biomass energy conversion by anaerobic microorganisms. Graphical abstract: Image, graphical abstract